Proceedings of the 12th European Conference on Software Architecture: Companion Proceedings 2018
DOI: 10.1145/3241403.3241450
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of dynamic trust contracts for industry 4.0 systems

Abstract: Due to their close relation to physical and virtual entities (humans, machines, processes, etc.) including their changing state and context, modern cyber-physical and IoT systems exhibit a high degree of architectural dynamicity. While sharing of data among all the entities of the system is the key driver to the efficiency of the system, it is at the same time necessary to effectively control which data are shared, with whom, and in which context so as to prevent potential misuse. The problem however is that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Al-Ali et al [162] describe a real-world use case for data flow monitoring, where certain data on machine error rates is shared within the company itself, and across organization boundaries based on a set of privacy policies. Some of these policies cannot be statically enforced because they depend on dynamically changing processes or coordinated interaction between different entities.…”
Section: ) Data Transportmentioning
confidence: 99%
“…Al-Ali et al [162] describe a real-world use case for data flow monitoring, where certain data on machine error rates is shared within the company itself, and across organization boundaries based on a set of privacy policies. Some of these policies cannot be statically enforced because they depend on dynamically changing processes or coordinated interaction between different entities.…”
Section: ) Data Transportmentioning
confidence: 99%
“…Another area of contention is the exchange of knowledge over dynamic networks in both industrial and non-industrial atmospheres (i.e., IT) given that the two atmospheres are geographically or logically isolated. In the age of Industry 4.0, data sharing between the OT and IT environments is essential for making the optimal business decisions (i.e., usually higher management is located in a different facility than current operations) [17]. However, this raises the vulnerability of such sensitive infrastructure, which can be exposed to untrustworthy networks and attacks.…”
Section: Relation Between Cybersecurity and Safety In Ahsmentioning
confidence: 99%
“…The dynamic nature of the CPS portion, such as a complex environment, necessitates a unique approach (i.e., considering cybersecurity and safety). Most data exchange methods, according to [17], are incapable of grasping highdynamic scenarios in which several parties (i.e., vendors) cooperate to achieve a shared purpose, particularly where privacy is factored in. The same authors suggested a solution based on establishing a dynamic trust zone in which decisions are automatically made through identifying flows, evaluating them, and deciding whether to allow the flow or not [17].…”
Section: Relation Between Cybersecurity and Safety In Ahsmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes the rules explicit and avoids ad-hoc interdependencies of constituent legacy systems. The approach is based on our preliminary work [2,3], where we have defined security ensembles that describe permitted interactions in the system and follow the system during its evolution. The approach presented in this paper brings it to the level of a self-adaptive architecture, introduces the concepts of the security adaptation controller and connects it to the legacy systems.…”
Section: Introductionmentioning
confidence: 99%